'Peopling' geographies of peace: the role of the military in peacebuilding in the Philippines. Issue 1 (30th April 2014) - Woon, Chih Yuan
<x xml:space="preserve">Abstract</x> Geographical forays into peace research have flourished in recent years. Without denying the value of these works in highlighting the discipline's normative and practical contributions towards peace, this paper calls for further interrogations into the peoples who are involved in the (re)making of peaceful geographies. Using the case study of the military in the southern Philippines, I showcase the efforts of a particular group of soldiers in harnessing coalitional formations with local communities and NGOs for peaceful outcomes. Specifically, such collaborative partnerships enabled meaningful dialogues and negotiations to take place so as to pave the way for the attainment of truly sustainable peace. Hence, I contend that moving towards 'peopled' accounts of peace can proffer insights into the relationships and interactions between actors and how these facilitate transformative possibilities for peace. This will in turn create space for reflecting on the motivations and pathways in practising and realising peace. Such an actor‐centred approach to peace is particularly important at this political juncture when attempts are made to shift geography away from its traditional interest in warfare so as to grant new visibility to alternative peace cultures – it not only highlights the discipline's ethical responsibility towards peace and nonviolence but also facilitates academic action that is embodied and engaged.